Metabolic profile of goats fed diets containing crude glycerin from biodiesel production - Bezerra, Higor Fábio Carvalho; Santos, Edson Mauro; de Carvalho, Gleidson Giordano Pinto; de Oliveira, Juliana Silva; da Silva, Fabiano Ferreira; Cassuce, Meiry Rodrigues; Guerra, Ricardo Romão; Pereira, Danillo Marte; Ferreira, Daniele de Jesus; Nascimento, Thiago Vinicius Costa; Zanine, Anderson de Moura (Frontiers in Veterinary Science, 2023)
Feedlot finishing of goats is a growing practice, but the economic viability of this technology is compromised by the inclusion of ingredients such as corn and soybean. An alternative to minimize this barrier is the use of agroindustry coproducts as substitutes for those ingredients, such as crude glycerol. This study aimed to evaluated the metabolism of crossbred Boer finishing goats fed diets containing crude glycerin from biodiesel production. Thirty-two crossbred, castrated goat of age were distributed in a fully randomized experimental design with four treatments and eight replicates. The experiment lasted 69 days, and goats were fed sorghum silage and concentrate, with the inclusion of crude glycerin in the diet at levels of 0, 50, 100, and 150 g/kg on a dry matter basis. The diets did not have an effect (p > 0.05) on the serum urea levels. Increasing dietary crude glycerin levels did not the influence the metabolic or urinary profiles (p > 0.05). The liver tissue of the goats fed diets containing the highest crude glycerin inclusion levels showed deleterious effects. The inclusion of crude glycerin with approximately 6.6 g/kg methanol caused deleterious effects to the liver tissue of Boer crossbred goats as the glycerin concentrations increased. However, glycerin levels did not cause deleterious effects on the liver tissue or on the serum or urinary profiles. The use of crude glycerin with lower methanol content is recommended for goat diets.